Macrophage Inhibition of Collagen-Induced Platelet Aggregation - Mørland, Berit (Thrombosis and Haemostasis, 1979)
Collagen was incubated with cells or media fractions of mouse peritoneal macrophage cultures, and its aggregating effect on human platelets was tested. Incubation with lysates of cultured cells completely abolished the normal collagen-induced platelet aggregation, while incubation with media fractions only caused partial inhibition. The latter inhibition was more pronounced after macrophage phagocytosis of latex particles, while endocytosis of endotoxin had no effect.Corresponding macrophage cultures were also tested for specific collagenase activity, using 14C-glycine labelled collagen as substrate. Collagenase activity was found in the culture media fractions only, and the enzyme activity could be enhanced by endocytosis of latex as well as endotoxin.It appears that the effect of macrophage lysates and media on collagen-platelet interaction cannot be ascribed only to secretion of collagenase from macrophages.